Taxation Ethical Issues: Perspectives of Tax Professionals in Indonesia - Irana Hertiningtyas; Andi Ina Yustina (The Indonesian Journal of Accounting Research, 2021)
This study aims to identify the ranking of taxation ethical issues regarding the frequency of occurrence and importance based on tax professionals' perspectives. Additionally, this study also examines the ethical climate of tax professionals in their practice. Questionnaires were distributed through a web-based survey and seminar. One hundred and sixty-seven useable questionnaires with a 29% respondent rate were analyzed. The results showed that tax avoidance is perceived as the most critical and frequent issue in Indonesia. Comparing the top 10 rankings of importance and occurrence issues, eight issues are added in both of the rankings, such as continuing to act, reporting position, tax audit, loophole seeking, tax minimization, technical competence, supervision of audit, and tax avoidance. The results also demonstrated that the examining professionals' ethical climate through peer reviews revealed that tax professionals have been living in an environment that they considered ethical, even though they believe that many opportunities exist for them to do unethical actions.